2021
DOI: 10.3390/app11072941
|View full text |Cite
|
Sign up to set email alerts
|

Holonic Reengineering to Foster Sustainable Cyber-Physical Systems Design in Cognitive Manufacturing

Abstract: Value chain is identified as the generator of the metabolic rift between nature and society. However, the sustainable value chain can mitigate and reverse this rift. In this paper, firstly, a review of the main digital enablers of Industry 4.0 and the current state of cognitive manufacturing is carried out. Secondly, Cyber-Physical Systems are conceived from the holonic paradigm, as an organizational enabler for the whole of enablers. Thirdly, the bijective relationship between holonic paradigm and container-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 130 publications
0
3
0
Order By: Relevance
“…Jiao et al (2021) pointed out that digital development plays an important role in promoting the realization of Industry 4.0 [36]. Martin-Gomez et al (2021) proposed that digitization and informatization are important factors for realizing the intelligent, connected and sustainable development of manufacturing industry [37]. Yin et al (2022) and Garcia et al (2022) agree with this statement [9,38].…”
Section: Literature Review and Mechanism Construction 21 Literature R...mentioning
confidence: 98%
“…Jiao et al (2021) pointed out that digital development plays an important role in promoting the realization of Industry 4.0 [36]. Martin-Gomez et al (2021) proposed that digitization and informatization are important factors for realizing the intelligent, connected and sustainable development of manufacturing industry [37]. Yin et al (2022) and Garcia et al (2022) agree with this statement [9,38].…”
Section: Literature Review and Mechanism Construction 21 Literature R...mentioning
confidence: 98%
“…Regarding their contribution to future industrial challenges, they have identified, studied, and classified reference HCA developed from 1998 to 2020 [1,2,5,6,7,8,9,10,11,24,25,26,27]. To these, we added some more recent works, posteriors to the reviews: the REDCA and EMH 2 architectures [28,29] and the holonic reengineering for CPS [30] propositions. From this first sample, 3 clear observations could be made:…”
Section: Hms and Hca: What Place For Humans?mentioning
confidence: 99%
“…Further, in advocating for the CE through renewable energy sources, the systems approach is extremely helpful on the issue of food security with the use of food crops for energy (e.g., corn for ethanol vs. corn for food and feed). However, holonic systems towards a digitally-enabled transition to the CE is an exciting innovation to look forward to, as discussed in the works of Ávila-Gutiérrez et al [61] and Martín-Gómez et al [62]. Such systems are among the numerous opportunities to innovate with the existing CE systems to pursue closing the loops more effectively.…”
Section: Systems Thinking Challenges and Ways Forwardmentioning
confidence: 99%